Antibodies from a Patient with Type 1 Diabetes and Celiac Disease Bind to Macrophages that Express the Scavenger Receptor CD163. (2011) - Sonier, Brigitte; Strom, Alexander; Wang, Gen-Sheng; Patrick, Christopher; Crookshank, Jennifer A; Mojibian, Majid; MacFarlane, Amanda J; Scott, Fraser W
Abstract : Antibodies against the wheat storage globulin Glo-3A from a patient with both type 1 diabetes (T1D) and celiac disease were enriched to identify potential molecular mimicry between wheat antigens and T1D target tissues. Recombinant Glo-3A was used to enrich anti-Glo-3A immunoglobulin G antibodies from plasma by batch affinity chromatography. Rat jejunum and pancreas, as well as human duodenum and monocytes were probed, and binding was evaluated by immunohistochemistry and confocal microscopy. Glo-3A-enriched antibodies bound to a specific subset of cells in the lamina propria of rat jejunum that co-localized mostly with a marker of resident, alternatively activated CD163-positive (CD163 + ) macrophages. Blood monocytes and macrophage-like cells in human duodenum were also labelled with the enriched antibodies. Blocking studies revealed that binding to CD163 + macrophages was not due to cross-reactivity with anti-Glo-3A antibodies, but rather to non-Glo-3A antibodies co-purified during antibody enrichment. The novel finding of putative autoantibodies against tolerogenic intestinal CD163 + macrophages suggests that regulatory macrophages were targeted in this patient with celiac disease and T1D.